ChemInform Abstract: C2‐Alkylation and Alkenylation of Indoles Catalyzed by a Low‐Valent Cobalt Complex in the Absence of Reductant. Issue 37 (August 2016) - Fallon, Brendan J.; Derat, Etienne; Amatore, Muriel; Aubert, Corinne; Chemla, Fabrice; Ferreira, Franck; Perez‐Luna, Alejandro; Petit, Marc
Abstract: The use of a well‐defined low‐valent cobalt complex for the functionalization of indoles in the absence of an external reductant or additives is described.